Enhanced membrane ion selectivity by incorporating graphene oxide nanosheet for vanadium redox flow battery application. (10th September 2017) - Wu, Chunxiao; Bai, Huijuan; Lv, Yang; Lv, Zhaoqian; Xiang, Yan; Lu, Shanfu
Graphical abstract: Abstract: High ion selectivity with high proton conductivity and low vanadium ionic permeability is one of the critical issues for an ideal ion conductive membrane (ICM) in vanadium redox flow battery (VRFB). In this work, a novel ICM is fabricated by-polyvinylpyrrolidone (PSF-PVP) membrane to enhance its membrane ion selectivity. Both the proton conductivity and vanadium ion permeability of the PSF-PVP/GO composite membranes are decreased with the loading of GO. However, the ion selectivity of the composite membranes shows volcano shape against the GO loading. After adding 0.05 wt% GO, the ion selectivity of the composite membrane reaches the highest point of 2.2 × 10 7  S cm 3 /min, which is 47% higher than that of the pristine PSF-PVP membrane. Incorporating graphene oxide nanosheet framework is of help to improve the membrane ion selectivity by size sieving effect, tortuous pathways and electrochemical exclusive behavior on vanadium ions. Moreover, a single battery with the optimized membrane exhibits coulumbic efficiency of 98% and energy efficiency of 87%, while the high efficiencies are also maintained during continuous running of 100 charge-discharge cycles. These convincing results indicate that the introduction of GO to the PSF-PVP membrane is promising and environmental friendly in VRFB application.